Biomimetic Scaffolds Regulating the Iron Homeostasis for Remolding Infected Osteogenic Microenvironment - Mengting Yin; Zhiqing Liu; Zhongyi Sun; Xinyu Qu; Ziyan Chen; Yuying Diao; Yuxuan Cheng; Sisi Shen; Xiansong Wang; Zhuyun Cai; Bingqiang Lu; Shuo Tan; et al. (Advanced Science, 2024)
Abstract The treatment of infected bone defects (IBDs) needs simultaneous elimination of infection and acceleration of bone regeneration. One mechanism that hinders the regeneration of IBDs is the iron competition between pathogens and host cells, leading to an iron deficient microenvironment that impairs the innate immune responses. In this work, an in situ modification strategy is proposed for printing iron‐active multifunctional scaffolds with iron homeostasis regulation ability for treating IBDs. As a proof‐of‐concept, ultralong hydroxyapatite (HA) nanowires are modified through in situ growth of a layer of iron gallate (FeGA) followed by incorporation in the poly(lactic‐co‐glycolic acid) (PLGA) matrix to print biomimetic PLGA based composite scaffolds containing FeGA modified HA nanowires (FeGA‐HA@PLGA). The photothermal effect of FeGA endows the scaffolds with excellent antibacterial activity. The released iron ions from the FeGA‐HA@PLGA help restore the iron homeostasis microenvironment, thereby promoting anti‐inflammatory, angiogenesis and osteogenic differentiation. The transcriptomic analysis shows that FeGA‐HA@PLGA scaffolds exert anti‐inflammatory and pro‐osteogenic differentiation by activating NF‐κB, MAPK and PI3K‐AKT signaling pathways. Animal experiments confirm the excellent bone repair performance of FeGA‐HA@PLGA scaffolds for IBDs, suggesting the promising prospect of iron homeostasis regulation therapy in future clinical applications.